Overcoming Discriminatory Attitudes – a Prerequisite for Women’s Participation in Economic Decision-Making - Šidlauskienė, Virginija; Pocevičienė, Rasa (Information & Media, 2020)
Although research has shown that women not only have the necessary education and professional qualifications, but also want and can hold positions in the highest decision-making bodies, gender disproportion in the boards of Lithuanian listed companies is obvious, since women have less favorable conditions than men since the beginning of their careers to pursue top management positions. One of the reasons for gender inequality in company boards is the prevalence of gender-based discriminatory attitudes in the professional environment both in Lithuania and in all EU countries, so women need to overcome many obstacles related to corporate behavior and business culture in order to realize their full professional potential. In order to find out the gender balance in Lithuanian listed companies, the opinion of companies‘ board members (women and men) about the situation and opportunities to become members of the board, the possibilities of increasing the participation of women in the boards, etc., an empirical study was carried out. Analysis of the results showed that, although in theory most respondents claim that there is no external barrier for competent women to be proposed and elected to the board of directors, publicly available, let there be covert, discriminatory clauses that create limiting factors for women’s participation in company boards, the overcoming of which is highly dependent on the activity of women themselves and the change in attitudes and attitudes available. We’ve summarized the challenges to achieving gender equity on boards and suggestions to address each of the challenges into four broad categories: boards themselves, women themselves, culture, and laws. One more challenge relates to the argument whether this idea of gender equity on Boards of Directors is even worth pursuing.
Keywords: Woman; participation in economic decision-making; discriminatory provisions; successful career; stock exchange board